2006
DOI: 10.1111/j.1399-3054.2006.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower seed deterioration as related to moisture content during ageing, energy metabolism and active oxygen species scavenging

Abstract: The objectives of the present work were to investigate whether loss of sunflower (Helianthus annuus L.) seed viability was affected by the embryo moisture content (MC) during seed pretreatment at 35°C, and was related to changes in energy metabolism and in the antioxidant defence system. Non-dormant seeds were equilibrated at MC of the embryonic axis ranging from 0.037 to 0.605 g H 2 O g 21 dry matter (DM) for 1 day at 15°C, and they were then placed at 35°C for various durations up to 14 days before the germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 45 publications
6
160
0
2
Order By: Relevance
“…Gidrol et al (1989) and Lehner et al (2007) did not find any increase in this compound during the accelerated aging of sunflower or wheat seeds. On the contrary, Goel et al (2003) or Kibinza et al (2006), for example, demonstrated that MDA accumulated during seed aging. The use of MDA as a marker of lipid oxidation has often been often subject to debate because this assay may be non specific and it does not measure hydroperoxides but the product of their degradation (Zacheo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Gidrol et al (1989) and Lehner et al (2007) did not find any increase in this compound during the accelerated aging of sunflower or wheat seeds. On the contrary, Goel et al (2003) or Kibinza et al (2006), for example, demonstrated that MDA accumulated during seed aging. The use of MDA as a marker of lipid oxidation has often been often subject to debate because this assay may be non specific and it does not measure hydroperoxides but the product of their degradation (Zacheo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, ROS production and lipid peroxidation have been reported to increase, along with moisture content, in response to artificial aging (Kibinza et al, 2006). Seeds possess higher concentrations of polyunsaturated fatty acids than other plant tissues (Mansfield and Briarty, 1992).…”
Section: Reactive Oxygen Species (Ros) and Signalingmentioning
confidence: 99%
“…For instance, the roles of reactive oxygen species (ROS) and anti-oxidative enzymes, PCD triggered by mitochondria and DNA alternation, molecular repairs (including DNA and protein), and epigenetic regulation are now beginning to be understood. Recently, it was reported that seed aging is related to cellular-level modifications, such as the loss of membrane integrity, RNA impairment, decreased energy metabolism and protein synthesis, and DNA degradation (McDonald, 1999;Corbineau et al, 2002;Kibinza et al, 2006;Ding et al, 2016); Osborne and Cheah (1978) and Osborne et al (1981) reported the degradation of embryonic nuclear DNA during seed aging.However, DNA laddering commonly observed in active and genetically controlled PCD or unaddressed deprivation after intensive DNA oxidation may lead to DNA impairment (Stein and Hansen, 1999;Slupphaug et al, 2003).…”
Section: Associated Changes Effects Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA) content is considered a biomarker of oxidative damage (Bailly et al, 1996) and is a commonly used method for the determination of lipid peroxidation (Cai et al, 2011); the accumulation of this compound is observed in the deterioration of lipid-rich seeds of some species, such as cotton (Goel, Goel, & Sheoran, 2003), sunflower (Kibinza, Vinel, Côme, Bailly, & Corbineau, 2006), and soybean (Sharma, Kaur, Bansal, & Gill, 2013).…”
Section: Introductionmentioning
confidence: 99%